Relationship between skeletal muscle mass and liver fibrosis markers for patients with hepatitis C virus related liver disease - Takata, Ryo (Medicine (Baltimore), 2017)
We aimed to elucidate the relationship between serum liver fibrosis markers (Mac-2 binding protein glycosylation isomer (M2BPGi), FIB-4 index, aspartate aminotransferase to platelet ratio index and hyaluronic acid), and skeletal muscle mass and to investigate factors linked to skeletal muscle mass loss (SMML) in patients with chronic hepatitis C (CHC, n = 277, median age = 64 years). We defined patients with psoas muscle index [PMI, sum of bilateral psoas muscle mass calculated by manual trace method at the lumber 3 level on the computed tomography images divided by height squared (cm(2)/m(2))] less than 6.36 cm(2)/m(2) for male and 3.92 cm(2)/m(2) for female as those with SMML based on the recommendations in current guidelines. Receiver operating curve (ROC) analysis was performed for predicting SMML in 4 liver fibrosis markers and parameters linked to SMML were also investigated in the univariate and multivariate analyses. In terms of liver fibrosis stages, F4 was observed in 115 patients, F3 in 67, F2 in 38, F1 in 53, and F0 in 4. The median (range) PMI for male and female were 6.198 (2.999–13.698) and 4.100 (1.691–7.052) cm(2)/m(2), respectively. There were 72 male patients with SMML (55.4%) and 58 female patients with SMML (39.5%) (P = .0112). In both male and female, a significant inverse correlation between PMI and levels of liver fibrosis markers was observed in all liver fibrosis markers. ROC analyses for predicting SMML revealed that FIB-4 index had the highest area under the ROC (AUC = 0.712), followed by M2BPGi (AUC = 0.692). In the multivariate analysis of factors linked to SMML, gender (P = .0003), body mass index (P < .0001), FIB-4 index (P = .0039), and M2BPGi (P = .0121) were found to be significant predictors. In conclusion, liver fibrosis markers, especially FIB-4 index, can be helpful for predicting SMML in CHC patients.